Growth performance and survival rate of planted dipterocarp species under artificial planting at Gunung Apeng Forest Reserve - Suzi Mellisa, Talip (Universiti Malaysia Sarawak, 2011)
A study was conducted in order to assess the growth performance and survival rate of planted Dipterocarp species under artificial planting at Gunung Apeng Forest Reserve. In this study, areas planted with Dryobalanops beccarii which were planted under line planting method were selected. Study sites were established in the reforestation areas (areas planted with Dryobalanops beccarii in the year 2005; D1305 and 2008; DB08). The growth performance at different age stand of planted Dryobalanops beccarii was evaluated by obtaining the measurement of the diameter, height and survival rate monthly since October 2010 for duration of six months. The findings showed that the mean annual increment in height (MAIH) and diameter (MAID) of planted Dryobalanops beccarii in DB05 showed better growth than DB08. In addition, the survival rate of Dryobalanops beccarii in DB05 and DB08 were similar at 86% and 84%, respectively. High survival rate and substantial growth performance of Dryobalanops beccarii indicates that microclimate condition in the study area affects the survival rate and growth performance of planted Dryobalanops beccarii.